Analisis Efektivitas Dan Efisiensi Anggaran Belanja - Raden Mas Rachmanninditya Dwifarchan; Umi Sulistiyanti (Jurnal Mutiara Ilmu Akuntansi, 2023)
The Regional Revenue and Expenditure Budget is the regional government's annual financial plan which is discussed and agreed upon jointly by the local government and the Regional People's Representative Council and stipulated by Regional Regulation. The budget is an important thing in running a business organization or government institution which can be a benchmark in a successful implementation of the business organization or government agency. In terms of the budget, it includes the APBD, in which each region is given the authority as well as the obligation to prepare the Regional Revenue and Expenditure Budget. With a good budget, it will make the performance of the organization run in a more structured and better manner, meaning that if the budget is effective and efficient then the targets to be achieved can be met. Effectiveness is an important thing that must be done in a job so that the goals that have been set can be achieved properly. Effectiveness is also interpreted as a key element in achieving the goals and targets set by an organization/agency. It means that it is said to be effective when the organization can achieve the goals and objectives as well as targets that have been previously designed. In general, efficiency means the absence of waste. Every activity that will be carried out in achieving a predetermined target, there is a need for efficiency in carrying out a job so that it can reach the predetermined target and can be carried out correctly and precisely.